Kajian Manajemen Keselamatan Proses dan Lingkungan - Sitepu, Dendi Eka Muda; Situmorang, Marningot Tua Natalis; Kholil, Kholil (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Process safety management is a set of administrative standards and regulations relating to occupational safety and health, especially for processes involving hazardous chemicals. This standard aims to prevent the release of chemicals that are toxic, reactive, flammable or explosive in large quantities. The main goal of a process safety management system is to protect workers, the surrounding community, and the environment, while also maintaining the safety of the business and existing assets. Process safety management involves implementing systems and principles to continuously identify potential hazards, assess their risks, and control the hazards associated with high-risk processes. Apart from that, this management also helps companies manage process safety risks and increase productivity and optimize business operations.